Mosque Library is a Source of Religious Literacy in Lombok Society - Nurul Hayati; Lolytasari Lolytasari (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: This study discusses the role of mosque libraries in strengthening religious literacy in the community. The study was conducted on mosque libraries in Lombok.Objective: This study aims to analyze the views of mosque library managers regarding the religious literacy of the surrounding community and explore the role of mosque libraries in strengthening religious literacy in the community.Methods: This study is an exploratory study with a qualitative approach. Data collection techniques were carried out through interviews with informants and observations. Data analysis was done through several stages: data reduction, presentation, and conclusion.Results: The study results indicate that mosque library managers in Lombok view the religious literacy of the surrounding community as a perfect religious awareness, primarily obtained from religious studies delivered orally by Tuan Guru in the community. In strengthening religious literacy, mosque libraries in Lombok generally have provided various religious literature on their library collection shelves but have not directly synergized with religious literacy activities organized by their mosques or Tuan Guru.Conclusion: This knowledge became an inspiring foundation for the development of mosque libraries as a source of religious literacy and support for local traditions developed by the people of Lombok.